Using the Internet registries to construct а structural model for locality estimation in the overlay networks - Poryev, G.V. (Реєстрація, зберігання і обробка даних, 2011)
The structure of the database files of the regional Internet registries is analyzed. With the help of proposed method for the locality class estimation is calculated the topological affinity for arbitrary address pairs without using any service traffic. The proposed locality class metric can be used as a distance substitute instead of the traditional trace and ping metrics to construct optimal overlay structure of the distributed and peer-to-peer networks. Проаналізовано структуру файлів бази даних регіональних реєстрів Інтернет. За допомогою запропонованого методу оцінки класу локальності обчислено топологічну близькість будь-яких пар адрес без використання службового трафіку. Запропоновану метрику локальності може бути використано як заміну традиційних метрик кількості вузлів і часу відклику для побудови оптимальних оверлейних структур у розподілених і однорангових мережах. Проанализирована структура файлов базы данных региональных реестров Интернет. С помощью предложенного метода оценки класса локальности вычисляется топологическая близость любой пары адресов без использования служебного трафика. Предложенная метрика локальности может быть использована как замена традиционным метрикам количества узлов и времени отклика для построения оптимальных оверлейных структур в распределенных и одноранговых сетях.